Determinants of Gender-Role Attitudes Among Japanese Regular Employees: A Generational Analysis of Adolescent Family Environment - Muto, Mami (Advances in Social Sciences Research Journal, 2026)
To understand and address gender inequality in Japan, it is necessary to clarify the processes through which individuals acquire traditional or egalitarian gender-role attitudes. Individuals likely learn and internalize gender-role attitudes by modeling the attitudes of parents and other family members within the household. Therefore, examining people's past family environments is essential for understanding the formation of gender-role attitudes. This study used a retrospective design to examine family environments during early adolescence (junior high school years). The sample consisted of regular full-time employees across Japan (N = 1,102, 552 men and 550 women, age range 20–61 years, Mage = 43.89, SD = 12.53). They were recruited through an online survey company. A multiple regression analysis using the mean gender-role attitude score as the dependent variable showed that current gender-role attitudes were significantly predicted by the perceived gender-role attitudes of the influential role model, whether the mother had held a managerial position, and age. The role model’s gender-role attitudes exerted the strongest effect. A three-way between-subjects (2 × 2 × 3) analysis of variance further revealed a significant two-way interaction effect. Among older participants in their fifties and sixties, having a mother who held a managerial position was associated with stronger egalitarian gender-role attitudes, particularly when the role model also held egalitarian values. In contrast, younger generations in their twenties exhibited more traditional attitudes toward gender roles. The study discusses potential socio-cultural and economic factors underlying this pattern.